Improvement of post-nickel mining soil fertility with biochar and calcite - Muhammad Jayadi; Kadar Wahid; Risma Neswati; Andri Andriansyah (Journal of Degraded and Mining Lands Management, 2022)
Reclamation of post-nickel mining soil requires a long process and renewable innovations to improve soil properties. One of the alternative technologies for post-mining soil reclamation is utilizing oil palm empty fruit bunches (OEFB) as biochar and applying calcite (CaCO3). The objective of this research was to determine the effect of OEFB and the application of CaCO3 on the properties of post- nickel mining soil and the growth of Mucuna sp. This research was a pot experiment using a factorial randomized block design method. Treatments tested were combinations of three OEFB biochar (B) levels, i.e., B1 = 2.5%, B2 = 5%, and B3 = 7.5% of soil weight, and three calcite (K) dosages, i.e., K1 = 1.5, K2 = 3, K3 = 4.5 t ha-1. The soil parameters measured included soil pH, available P, organic C, cation exchange capacity, and exchangeable Al, Ca, Mg, K, and Na. The parameters of Mucuna sp. measured were plant height and plant dry weight. The results showed that applying biochar and calcite to post nickel mining soil significantly increased soil pH, available P, organic C, cation exchange capacity, growth of Mucuna sp. and decreased exchangeable Al content. Treatment of biochar 7.5% by weight of soil and 4.5 t calcite ha-1 gave the best effect on improving soil fertility and growth of Mucuna sp. compared to other treatments.